2020
DOI: 10.1136/neurintsurg-2020-015978
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of ticagrelor as single antiplatelet therapy in prevention of thromboembolic complications associated with the Pipeline Embolization Device (PED): multicenter experience

Abstract: BackgroundFlow diversion (FD) is a common treatment modality for complex intracranial aneurysms. A major concern regarding the use of FD is thromboembolic events (TEE). There is debate surrounding the optimal antiplatelet regimen to prevent TEE. We aim to evaluate the safety and efficacy of ticagrelor as a single antiplatelet therapy (SAPT) for the prevention of TEE following FD for complex aneurysm treatment.MethodsA retrospective review of a prospectively maintained neuroendovascular database at three endova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…SAPT use with FD treatment is a new approach, and limited data are available in the literature. In a recent study, ticagrelor was used to prevent thromboembolic complications with Pipeline device (PED) as SAPT ( 10 ). Mohammaden et al demonstrated ticagrelor as a safe and effective antiplatelet in ruptured aneurysms with FDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAPT use with FD treatment is a new approach, and limited data are available in the literature. In a recent study, ticagrelor was used to prevent thromboembolic complications with Pipeline device (PED) as SAPT ( 10 ). Mohammaden et al demonstrated ticagrelor as a safe and effective antiplatelet in ruptured aneurysms with FDs.…”
Section: Discussionmentioning
confidence: 99%
“…However, hemorrhagic complications are a major concern during DAPT treatment in the acute setting of SAH. There have been limited data obtained from previous studies on single antiplatelet therapy (SAPT) in preventing thromboembolic complications associated with FDs ( 10 ). New-generation P2Y12 antagonist (ticagrelor and prasugrel) usage in neurointervention is a novel topic ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the application of FD application for IFCAs, the use of telescoping FDs with 25-30% overlap is often required to cover the entire IFCA (45). In addition, overlapping FDs can be employed for a greater flow-diverting effect (46). For this purpose, the new-generation double-layered FD is more useful (47).…”
Section: Fd Deploymentmentioning
confidence: 99%
“…For this purpose, the new-generation double-layered FD is more useful (47). However, this strategy must be used cautiously to avoid ischemia from perforator occlusion, especially in the BA or MCA (46,48). As a reconstructive technique, on rare occasions, it is necessary to combine FD deployment with the deconstructive approach.…”
Section: Fd Deploymentmentioning
confidence: 99%
“…Additionally, unlike clopidogrel or prasugrel, this drug does not require metabolic transformation, and receptor blockade generated by this drug is reversible. 17…”
Section: Dual Antiplatelet Regime (Dapr) and Anticoagulationmentioning
confidence: 99%